GOVERNMENT SUPPORT FOR ENTREPRENEURSHIP IN DEVELOPED COUNTRIES AND ADAPTATION OF EXPERIENCE IN THE REPUBLIC OF UZBEKISTAN - Rakhmatjanov Lazizkhan Turabayevich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The article examines the foreign experience of state support of small business in the largest foreign countries. The mechanisms of development of state support for small business in foreign countries are considered, the analysis of the level of development of small business in foreign countries and the Republic of Uzbekistan is given. The main directions and program activities on this issue have been identified and analyzed. The high socio-economic orientation of small and medium-sized businesses was noted.